A Cone-Beam Computed Tomography Scanning of the Root Canal System of Permanent Teeth among the Moscow Population - Svetlana Razumova; Anzhela Brago; Lamara Khaskhanova; Ammar Howijieh; Haydar Barakat; Ashot Manvelyan (Hindawi Limited, 2018)
Background. Successful endodontic treatment requires a significant knowledge of root canal anatomy. The aim of this study was to evaluate the root and root canal number of permanent teeth among the Moscow population using cone-beam computed tomography (CBCT) scanning. Materials and methods. 300 CBCT images of subjects were analyzed to study the anatomy of roots and root canal system of each tooth. The collected data were analyzed using IBM SPSS statistics software 22.0 version. Results. The maxillary incisors and canines had one root with one canal in 100%. Maxillary premolars had one root with one or two canals and two roots with two canals, while mandibular premolars were single-rooted with one or two canals. Maxillary first and second molar had three separated roots, and the prevalence of four canals was more often in first molars. Mandibular molars had two roots with different number of canals. Conclusion. The root canal system varies greatly among populations and even in different individuals within the same population; thus, using CBCT scanning is an effective technique in investigating the root canal system.